2007
DOI: 10.5458/jag.54.187
|View full text |Cite
|
Sign up to set email alerts
|

Saccharide and Fructooligosaccharide Contents, and Invertase, 1-KHE, 1-SST, 1-FFT and 6G-FFT Activities in Green Asparagus Spears during Storage: Effects of Temperature and Spear Portion

Abstract: Unlike most vegetable crops, asparagus, a hardy perennial plant, is commonly consumed and appreciated because it is low in calories and provides substantial amounts of reducing sugars and a very low amount of fructooligosaccharides (FOS), and these fructosyl polymers are well known for their health benefits.1) The chemical characteristics of the spears are markedly affected by temperature, 2) growth conditions 3) and harvest date. 4) Carbohydrates are major constituents of asparagus spears and contribute consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The highest content was found in fibres obtained after intense treatment with ethanol (I/E), with the rest of the fibres having almost the same fructan content. Fructans present in asparagus were mainly fructooligosaccharides (FOS -with low polymerisation degree) instead of inulin (high molecular weight) (Shiomi et al, 2007). FOS content of asparagus by-product was around 4 mg/g of dry weight (data not shown) and during the fibre obtaining process, it decreased between 25% and 95%, a reduction that was explained by the high solubility of these low molecular weight carbohydrates (3-4 polymerisation degree) in water/ethanol mixtures, even at room temperature.…”
Section: Fructansmentioning
confidence: 99%
“…The highest content was found in fibres obtained after intense treatment with ethanol (I/E), with the rest of the fibres having almost the same fructan content. Fructans present in asparagus were mainly fructooligosaccharides (FOS -with low polymerisation degree) instead of inulin (high molecular weight) (Shiomi et al, 2007). FOS content of asparagus by-product was around 4 mg/g of dry weight (data not shown) and during the fibre obtaining process, it decreased between 25% and 95%, a reduction that was explained by the high solubility of these low molecular weight carbohydrates (3-4 polymerisation degree) in water/ethanol mixtures, even at room temperature.…”
Section: Fructansmentioning
confidence: 99%
“…They also showed the metabolizing enzymes of these fructo oligosaccharides play a role in the balance of sugars between the bottom and the top of the spears where high catabolic activities were observed. 48) These results suggest that high fructo oligosaccharede content in asparagus spears may extend the rapid decline of sugars in the top portion. …”
Section: Enzymatic Preparation Of Fructo-oligosaccharidesmentioning
confidence: 74%
“…40) However, nothing has been reported for the metabolism of fructo oligosaccharides except the work of Shiomi et al . 48) The results showed that only short chain fructo oligosaccharides (1 kestose and nystose) are present and their contents in the spears is very low compared to those of glucose, fructose and sucrose. They also showed the metabolizing enzymes of these fructo oligosaccharides play a role in the balance of sugars between the bottom and the top of the spears where high catabolic activities were observed.…”
Section: Enzymatic Preparation Of Fructo-oligosaccharidesmentioning
confidence: 91%
“…Based on the water content of samples and HPLC chromatogram, consentration of FOS and saccharides yacon tubers samples can be identified, as showed in There was a research finding that, after 12 days of shade storage, FOS concentration of yacon tubers were decreased from 50-62 to 27-37% of dry weight, while the concentration of saccharides increased from 29-34 to 48-52%. During the six days sunlight exposure, FOS concentrations were decreased from 50-62 to 29-44% and saccharides increased from 29-34 to 45-51% of dry weight 17 .…”
Section: The Effect Of Storage and Boiling Time To Yacon Tubers Oligosaccharides Contentmentioning
confidence: 94%